PO:29:145 | Fibromyalgia in idiopathic inflammatory myopathies: is it time for rheumatologists to investigate it? Federico Fattorini1, Michele Diomedi1, Simone Barsotti2, Elenia Laurino3, Chiara Cardelli1|4, Alessandra Tripoli3, Linda Carli3, Marta Mosca1|3. | 1Rheumatology Unit, Department of Clinical and Experimental Medicine, University of Pisa, Pisa, Italy; 2Rheumatology, Versilia Hospital, Viareggio, Italy; 3Rheumatology Unit, AOUP, Pisa, Pisa, Italy; 4Department of Medical Biotechnologies, University of Siena, Siena, Italy. (Reumatismo, 2025)
Background. Fibromyalgia (FM) is a complex syndrome characterised by chronic pain, fatigue and functional symptoms; it is often accompained by mood disorders. FM affects, on average, 2.3% of the European population with a profound impact on both physical and social aspects of quality of life (QoL). FM is known to be a frequent comorbidity in Connective Tissue Diseases (CTDs). Few data are available at present about the prevalence of FM in Idiopathic Inflammatory Myopathies (IIMs) and about the profile of IIM patients with FM. The objective of the study was to determine the prevalence of FM in a monocentric cohort of IIMs patients, evaluating possible correlations with clinical features, disease activity and parameters of QoL. Materials and Methods. We retrospectively analyzed medical records of consecutive patients diagnosed with IIM according to the EULAR/ACR 2017 criteria and regularly followed at our specialistic outpatient Myositis Clinic. We collected data about demography, subset and disease duration, organ involvement, autoantibody profile and comorbidities. Patients’ QoL was investigated through the following Patient Reported Outcomes (PROs): Short Form 36 (SF36), Hospital Anxiety and Depression Scale (HADS), Health Assessment Questionnaire (HAQ). The diagnosis of FM was confirmed following the 2016 American College of Rheumatology Fibromyalgia Diagnostic Criteria. Intergroups comparisons were assessed by using Chi-square, t-test and ANOVA. P values <0.05 were considered significant. Results. A total of 184 patients were enrolled, 119 (64,7%) female, with a mean age of 66,5±11.2 years and a mean disease duration of 9.9±5.2 years. Twenty-three patients (12,5%) had FM, all of them were female. Taking into account epidemiological and clinical characteristics of patients, a diagnosis of FM was significantly associated with female sex (p<0.001), muscular involvement (p=0.015), lung involvement (p=0.036), sicca syndrome (p=0.004). Regarding comorbidities, a significant correlation was highlighted between FM and obesity (p=0.024), osteopenia (p=0.026) and thyroid dysfunction (p=0.05). PROs analysis showed patients with FM had significantly higher values of HAQ (p=0.005) and significantly lower values on different items of SF36 (Physical Function p=0.019, Bodily Pain p=0.006, Vitality p=0.026). Conclusions. Our data showed, as expected, that the prevalence of FM in IIMs patients was higher than in the general population and similar to that of other CTDs (4,5). Moreover, these results confirm the deep relationship between FM and both female gender, sicca syndrome and thyroid dysfunctions. However, they also showed a higher risk of FM in IIMs patients with muscle or pulmonary involvement, or with a reduced bone mineral density, or in obese patients. PROs’ analysis confirmed a significant impact of FM on both physical and mental outcomes of IIM patients. Although preliminary, these results could help rheumatologists in profiling the characteristics of FM patients in IIMs in their routinary assessment, thus aiming at improving the management of this potentially disabling condition.